التأمين البحري في الجزائر - بالي, حمزة; حناشي, بورني (جامعة الوادي - University of Eloued, 2020)
يعتبر النقل البحري الذي يتحمل مسؤولية نقل 90% من إجمالي حجم التجارة العالمية هو بحق شريان الاقتصاد العالمي, ولنا أن نتخيل أنه بدون النقل البحري سوف نكون عاجزين عن إنجاز المعاملات التجارية بين مختلف قارات العالم. لكن عملية النقل البحري لا تخلو من مشاكل بسبب الأخطار الخاصة التي تواجه الرحلة البحرية، وبسبب حجم الأضرار المرتبطة بالحوادث البحرية التي تتعرض لها السفن وحمولتها أثناء عملية النقل, وما يميز هذا الأخطار الجسامة, مما ينتج عنها خسارة كبيرة. تهدف هذه الدراسة إلى الإسهام في كل ما من شأنه تحقيق سلامة عمليات التجارة الخارجية وهذا من خلال إبراز دور التأمين البحري في إيجاد آليات تضمن تغطية المخاطر البحرية في الجزائر, حيث يعتبر التأمين في هذا المجال من أفضل الوسائل لإدارة الأخطار, لما له من أهمية بارزة في مجال التجارة الدولية والنقل البحري, بحيث أصبح من النادر أن تبحر سفينة أو تنقل بضاعة أو يقدم بذلك بنك على عملية من عمليات التجارة الخارجية دون وجود وثيقة تأمين. Maritime transport, which is responsible for the transfer of 90% of the total volume of world trade, is truly the linchpin of the global economy, and we can imagine that without shipping we will be unable to complete business transactions between different continents of the world. However, the maritime transport process is not without problems because of the special risks facing the maritime voyage and because of the magnitude of the damage associated with marine accidents to which ships and their cargo are exposed during the transport process, What distinguishes this grave dangers, which results in a great loss. This study aims to contribute to everything that would achieve the safety of foreign trade operations and this by highlighting the role of marine insurance in finding mechanisms to ensure coverage of marine risks, as insurance in this area is one of the best means for managing risks, because of its outstanding importance in the field of trade International and maritime transport, so that it has become rare for a ship to sail or to transport goods or to provide a bank for foreign trade operations without an insurance policy
Marine Insurance in Algeria
مقال
Keywords: النقل البحري ; الأخطار البحرية ; التأمين البحري ; الجزائر